Fatal stagger poisoning by consumption of Festuca argentina (Speg.) Parodi in goats from Argentine Patagonia - Martinez, Agustin; Cook, Daniel; Lee, Stephen T.; Sola, Diego; Bain, Luciana; Borrelli, Laura Beatriz; Acín, Cristina; Gardner, Dale R.; Robles, Carlos Alejandro (Elsevier, 2020)
The present study describes the spontaneous and experimental poisoning of goats by Festuca argentina in Argentine Patagonia. In April 2017, eight seven-month-old Creole male goats were accidentally introduced into a paddock that contained F. argentina. After four days, two of the goats were found dead and four out of the six remaining goats were clinically affected. Two of the latter had to be later euthanized in extremis. The main clinical signs were progressive nervous signs, starting with moderate muscle tremors, wide-based stance and ataxia. Postmortem examination was performed on the two euthanized goats. Epidermal fragments of F. argentina were found in the rumen samples from the necropsied goats and the fecal samples from the four affected goats. For the experimental poisoning, fresh sheaths of F. argentina collected from the paddock were offered to two goats at 10 g/kg body weight for 3 days. After 24–36 h, both animals exhibited severe muscle tremors, reluctance to move, tetanic convulsions, and opisthotonus. In both the spontaneously and experimentally poisoned goats, gross lesions were similar and consisted of dehydration, petechial hemorrhages in the epicardium and congestion. The main microscopic findings consisted of degeneration and loss of Purkinje cells and torpedoes in the granular layer of the cerebellum. The F. argentina sheaths collected from the pasture were found to contain tremorgenic indole-diterpene alkaloids. Taken together, the results of the present study suggest that the tremorgenic syndrome observed in the spontaneously poisoned goats was due to poisoning by F. argentina.